Penerapan Prinsip Keterbukaan dalam Laporan Keuangan PT Hanson International Tbk Berdasarkan Undang-Undang No. 8 Tahun 1995 - Muhamad Bintang Sahmada; Toto Tohir Suriaatmaja (Bandung Conference Series: Law Studies, 2024)
Abstract. Service providers that play an important role in society are financial services, especially in the capital markets sector. Every company registered on the stock exchange, which becomes a public company, is required to carry out activities in the capital market guided by the principles of openness, including in the annual financial report (LKT). The application of the principle of transparency in the capital market is realized by analyzing Law No. 8 of 1995 supported by POJK regulations POJK14/POJK.04/2022 and POJK 31 /POJK.04/2015. One case related to manipulation of financial reports that did not apply the principle of transparency occurred in PT's annual financial report. Hanson International Tbk which was carried out by the Company Director with the initials BJ. The manipulation of financial reports was carried out by falsifying data records in the financial reports and using the full accrual method in recording the company's financial reports. The research results show that the application of the principles of openness implemented in the analysis of Law No. 8 of 1995 is supported by POJK regulations POJK14/POJK.04/2022 and POJK 31 /POJK.04/2015 on PT's annual financial reports. Hanson International Tbk has not complied with the guidelines for implementing financial reports, resulting in losses for investors. In this case PT. Hanson International Tbk committed unlawful acts based on Article 1365 of the Civil Code. Apart from that, BJ as Director violated the provisions in Law No. 8 of 1998 concerning capital markets. Abstrak. Penyedia layanan yang memainkan peran penting dalam masyarakat adalah layanan keuangan, terutama di sektor pasar modal. Setiap perusahaan yang terdaftar di bursa saham dan menjadi perusahaan publik diwajibkan untuk melaksanakan kegiatan di pasar modal yang dipandu oleh prinsip keterbukaan, termasuk dalam laporan keuangan tahunan (LKT). Penerapan prinsip transparansi di pasar modal diwujudkan dengan menganalisis Undang-Undang No. 8 Tahun 1995 yang didukung oleh peraturan POJK POJK14/POJK.04/2022 dan POJK 31/POJK.04/2015. Salah satu kasus terkait manipulasi laporan keuangan yang tidak menerapkan prinsip transparansi terjadi pada laporan keuangan tahunan PT. Hanson International Tbk yang dilakukan oleh Direktur Perusahaan berinisial BJ. Manipulasi laporan keuangan dilakukan dengan memalsukan catatan data dalam laporan keuangan dan menggunakan metode akrual penuh dalam pencatatan laporan keuangan perusahaan. Hasil penelitian menunjukkan bahwa penerapan prinsip keterbukaan dalam analisis Undang-Undang No. 8 Tahun 1995 didukung oleh peraturan POJK POJK14/POJK.04/2022 dan POJK 31/POJK.04/2015 pada laporan keuangan tahunan PT. Hanson International Tbk belum mematuhi pedoman pelaksanaan laporan keuangan, yang mengakibatkan kerugian bagi investor. Dalam hal ini, PT. Hanson International Tbk melakukan perbuatan melawan hukum berdasarkan Pasal 1365 Kitab Undang-Undang Hukum Perdata. Selain itu, BJ sebagai Direktur melanggar ketentuan dalam Undang-Undang No. 8 Tahun 1998 tentang pasar modal.